1998
DOI: 10.1001/jama.280.5.443
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Torture on Refugees Displaced Within the Developing World

Abstract: Context.-Most of the world's refugees are displaced within the developing world. The impact of torture on such refugees is unknown. Objective.-To examine the impact of torture on Bhutanese refugees in Nepal. Design.-Case-control survey. Interviews were conducted by local physicians and included demographics, questions related to the torture experienced, a checklist of 40 medical complaints, and measures of posttraumatic stress disorder (PTSD), anxiety, and depression. Setting.-Bhutanese refugee community in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
149
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(178 citation statements)
references
References 54 publications
23
149
1
5
Order By: Relevance
“…Multiple studies have demonstrated high rates of somatic symptoms in trauma victims (Lin and Cheung, 1999;Shrestha et al, 1998;Van Ommeran et al, 2001). Results of the present study support the hypothesis that Rwandan holocaust survivors frequently experience the sudden onset of somatic symptom(s) that form part of a panic attack.…”
Section: Discussionsupporting
confidence: 85%
“…Multiple studies have demonstrated high rates of somatic symptoms in trauma victims (Lin and Cheung, 1999;Shrestha et al, 1998;Van Ommeran et al, 2001). Results of the present study support the hypothesis that Rwandan holocaust survivors frequently experience the sudden onset of somatic symptom(s) that form part of a panic attack.…”
Section: Discussionsupporting
confidence: 85%
“…These differences between the studies are difficult to interpret, but may have to do with sample differences (Holtz's respondents were predominantly nuns). The study of Bhutanese refugees in Nepal (Shrestha et al, 1998) revealed a similar pattern to ours, with nearly one third of the respondents reaching the cutoff point for substantial emotional distress. The proportion of respondents that endorsed anxiety was 38%, whereas substantial symptoms of depression were reported by 20%.…”
Section: Discussionsupporting
confidence: 83%
“…Shocking nearly everyone in the West, many African girls eagerly await traditional coming-of-age ceremonies in which their genitalia are carved up by older women (Obermeyer, 1999;Shweder, 2000). Conversely, compelling Hindus to violate religious taboos by forcing them to eat pork and beef is a common method of torture in Bhutan (Shrestha et al, 1998).…”
Section: Criterion a And The Central Paradox Of Ptsdmentioning
confidence: 99%